Metformin and cancer mortality - Lev Mikhaylovich Bershteyn (Сахарный диабет)
The author analyses recent publications supporting the ability of metformin to decrease the risk of cancer morbidity and mortality in patients with type 2diabetes mellitus. Pre-history of the problem (including the use of biguanides for metabolic rehabilitation of oncological patients), the role of DM as a riskfactor of cancer morbidity and mortality, mechanisms and targets of metformin anticancer effects, and potential use of this agent in non-diabetic patientsare discussed. The need for the search of the markers of sensitivity and resistance to metformin to be used in oncological practice is emphasized.